A scheme for controlled islanding to prevent subsequent blackout - Ahmed, S.S.; Sarker, N.C.; Khairuddin, A.B.; Ghani, M.R.B.A.; Ahmad, H. (2003)

(untitled)
The power systems operated by the utilities in developing countries suffer from a large gap between demand and generation, inadequate transmission capacity, and nonuniform location of the load centers and generating stations. Occurrences of faults in such systems, in most of the cases, end up with the worst consequences (i.e., complete blackout). This paper illustrates the way a blackout can be prevented in real time through controlled segregation of a system into a number of viable islands together with generation and/or load shedding. The nature and location of any fault that warrants such islanding can be ascertained in real time through monitoring the active-power (megawatt) flows at both ends of a number of prespecified lines. The blackout of June 20, 1998 in the Bangladesh Power Development Board system has been used as an example in the illustration. The philosophy of the proposed islanding scheme may be considered for implementation in other power systems also.